Hole transport material containing crown ether structure and preparation method thereof
By using hole transport materials containing crown ether structures to coordinate with Li+ ions in perovskite solar cells, the hygroscopicity and solubility of Li-TFSI dopants are solved, and the stability of perovskite solar cells is improved and Performance, achieving high efficiency comparable to classic combinations.
Patent Information
- Application Number
- CN202310215758.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-08
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-03-08
AI Technical Summary
In perovskite solar cells, the hygroscopicity and solubility problems of Li-TFSI dopants lead to perovskite crystal degradation and the quality of hole transport layer decreases, and Li+ migration leads to a hysteresis effect, affecting device stability.
The hole transport material containing crown ether structure is used to suppress its migration and moisture absorption by coordination with the Li+ ion host and guest, and a hole transport layer is prepared by spin coating to enhance the stability of perovskite solar cells.
It effectively improves the solubility of Li-TFSI, inhibits its aggregation and migration, improves the stability and performance of perovskite solar cells, and maintains the high efficiency of the Spiro-OMeTAD/PTAA+Li-TFSI combination.
Smart Images

Figure CN116239563B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a hole transport material containing a crown ether structure and a preparation method thereof. Background Art
[0002] Since the advent of organic-inorganic hybrid perovskite solar cells, the photoelectric conversion efficiency of the device has increased from the initial 3.8% to the current 26.08%, showing great development potential. Compared with traditional silicon-based solar cells, the manufacturing cost is low and it has good commercial prospects. Hole transport materials are an important component of perovskite solar cells. Their main function is to block electrons and collect holes injected by the perovskite light-absorbing layer and transfer them to the metal electrode to achieve effective separation of electrons and holes. Their hole transport performance is one of the key factors determining the photovoltaic performance of perovskite solar cells. Today, the most widely used organic hole transport materials in perovskite solar cells are mainly Spiro-OMeTAD and PTAA. However, the intrinsic conductivity of these two materials is poor, and dopants are usually required to improve their hole transport ability to ensure the high energy conversion efficiency of perovskite solar cells. Among them, Li-TFSI is the most widely used p-type hole dopant, but Li-TFSI doping will bring the following problems: (1) The hygroscopicity of Li-TFSI will accelerate the degradation of perovskite crystals; (2) Li-TFSI has low solubility in organic solvents (chlorobenzene, chloroform, etc.), causing it to aggregate in the film and affecting the quality of the hole transport layer film; (3) Li + It will migrate to other functional layers, resulting in hysteresis effect. How to effectively solve the above problems is of great significance to achieve the long-term stability of perovskite solar cells.
[0003] At present, the following methods are mainly used to solve the above problems of Li-TFSI: (1) Develop new dopants to replace Li-TFSI. For example, Lewis acid LAD and ionic liquid EIm-TFSI are used as p-type dopants to replace Li-TFSI respectively to obtain a hole transport layer with excellent performance and stability. (2) Develop new non-doped hole transport materials. For example, the new ionic self-doped hole transport material M7-TFSI and the non-doped hole transport materials SFX-DTF1 and SFX-DTF2 based on DTF groups to obtain efficient and stable battery device performance. Although these methods have achieved certain results, they are still not comparable to the classic combination of Spiro-OMeTAD / PTAA+Li-TFSI. Therefore, it is particularly important to propose a solution that can solve the negative effects of Li-TFSI doping while retaining the high efficiency of the classic combination of Spiro-OMeTAD / PTAA+Li-TFSI. Summary of the invention
[0004] The purpose of the present invention is to provide a hole transport material containing a crown ether structure and a preparation method thereof in view of the defects of the background technology. The hole transport material provided by the present invention has a crown ether structure that can react with Li + ions to coordinate with the host and guest, inhibiting the Li + migration and moisture absorption, thereby effectively improving the stability of perovskite solar cells.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A hole transport material containing a crown ether structure, whose chemical structure is:
[0007]
[0008] Wherein, n=1, 2 or 3; X is selected from one or more of O, S, Se or NH.
[0009] The present invention also provides a method for preparing a hole transport material containing a crown ether structure, comprising the following steps:
[0010] Step 1, according to the molar ratio of 1: (9.51-10.6): (7.77-8.57): (0.26-0.38): (0.58-0.66), 2,2',7,7'-tetrabromo-9,9'-spirobifluorene, 4-methoxyaniline, sodium tert-butoxide, tri(dibenzylideneacetone)dipalladium, and tri(tert-butyl)phosphine are sequentially added into a nitrogen-protected three-necked flask, and anhydrous toluene is added to fully dissolve the above reactants; the obtained reaction mixture is stirred at 90-150° C. for 20-40 hours under nitrogen protection, and after completion, it is cooled to room temperature, filtered, and purified by silica gel column chromatography to obtain compound 1;
[0011] Step 2, according to the molar ratio of 1: (4.98-5.97): (3.98-4.72): (0.29-0.41): (0.62-0.66), compound 1, a material containing a crown ether group, sodium tert-butoxide, tri(dibenzylideneacetone)dipalladium, and tri(tert-butyl)phosphine are added to a three-necked flask protected by nitrogen in sequence, and anhydrous toluene is added to fully dissolve the above reactants; the obtained reaction mixture is stirred at 90-150° C. for 20-40 hours under nitrogen protection, and after completion, it is cooled to room temperature, filtered, and purified by silica gel column chromatography to obtain the hole transport material containing the crown ether structure.
[0012] Furthermore, the crown ether group-containing material in step 2 is 4-bromobenzo-12-crown 4-ether, 4-bromobenzo-15-crown 5-ether, 4-bromobenzo-18-crown 6-ether, or a material in which one or more oxygens of the crown ether group in the above materials are replaced by sulfur, nitrogen or selenium.
[0013] The present invention also provides a method for preparing a hole transport layer based on a hole transport material containing a crown ether structure, comprising the following steps:
[0014] Step 1, adding the hole transport material containing the crown ether structure prepared above into an organic solvent, stirring and mixing evenly to obtain a mixed solution A with a mass concentration of 60 to 120 mg / mL;
[0015] Step 2, adding Li-TFSI to the mixed solution A obtained in step 1, stirring and mixing evenly to obtain a mixed solution B; wherein the molar ratio of the hole transport material to Li-TFSI is 1: (0.02-0.08);
[0016] Step 3: Spin coating the mixed solution B obtained in step 2 onto the perovskite light absorbing layer at a spin coating speed of 2000 to 4000 rpm for 20 to 40 seconds to obtain the hole transport layer.
[0017] Furthermore, the organic solvent in step 1 is chlorobenzene, dichlorobenzene, chloroform, toluene, etc.
[0018] The present invention also provides a perovskite solar cell, comprising a conductive substrate, an electron transport layer, a perovskite light absorbing layer, a hole transport layer and a metal electrode arranged in sequence, wherein the hole transport layer is the hole transport layer prepared by the above method.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention provides a hole transport material containing a crown ether structure, wherein the crown ether structure can be combined with Li + The host-guest coordination is formed to promote the dissolution of Li-TFSI in organic solvents (chlorobenzene, chloroform, etc.), effectively preventing the aggregation of Li-TFSI; at the same time, it can also effectively improve the hygroscopicity of Li-TFSI and inhibit the formation of Li + The crown ether structure can also passivate the lead defects on the surface of perovskite, reduce the water and oxygen adsorption sites, and further improve the stability of perovskite solar cells. The synthesis process of the hole transport material with crown ether structure is simple and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A synthetic route for the hole transport material containing a crown ether structure provided by the present invention;
[0022] Figure 2 High resolution mass spectrum of the hole transport material prepared in Example 1;
[0023] Figure 3A schematic diagram of the structure of a perovskite solar cell based on a hole transport material containing a crown ether structure provided by the present invention;
[0024] Figure 4 This is a performance comparison diagram of the perovskite solar cells prepared in Example 2 (Spiro-ce) and Comparative Example 1 (Spiro-OMeTAD);
[0025] Figure 5 This is a performance comparison chart of the perovskite solar cell prepared in Example 2 after being placed for 1 hour and 120 hours. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific embodiments.
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0028] Example 1
[0029] A method for preparing a hole transport material Spiro-ce containing a crown ether structure, such as Figure 1 As shown, the following steps are included:
[0030] Step 1, 2,2',7,7'-tetrabromo-9,9'-spirobifluorene (3 g, 4.75 mmol), 4-methoxyaniline (5.85 g, 47.47 mmol), sodium tert-butoxide (3.65 g, 6.47 mmol), tris(dibenzylideneacetone)dipalladium (1.3 g, 1.42 mmol), tri(tert-butyl)phosphine (0.58 g, 2.85 mmol) were sequentially added to a 150 mL three-necked flask protected by nitrogen, and then 40 mL of anhydrous toluene was added; the obtained reaction mixture was stirred at 120° C. for 30 h under nitrogen protection, and after completion, it was cooled to room temperature, filtered, and purified by silica gel column chromatography (with ethyl acetate / n-hexane = 40% (volume ratio) as eluent) to obtain compound 1 (2.16 g, 58% yield);
[0031] Step 2, compound 1 (1.3 g, 1.62 mmol), 4-bromobenzo-15 crown 5-ether (2.21 g, 8.09 mmol), sodium tert-butoxide (0.62 g, 6.47 mmol), tri(dibenzylideneacetone)dipalladium (0.44 g, 0.49 mmol), tri(tert-butyl)phosphine (0.2 g, 0.97 mmol) were added sequentially to a 150 mL three-necked flask protected by nitrogen, and then 25 mL of anhydrous toluene was added; the obtained reaction mixture was stirred at 120 ° C for 30 h under nitrogen protection. After completion, it was cooled to room temperature, filtered, and purified by silica gel column chromatography (with methanol / dichloromethane = 10% (volume ratio) as eluent) to obtain the hole transport material Spiro-ce containing the crown ether structure (1.3 g, 43% yield).
[0032] Example 2
[0033] The preparation method of a perovskite solar cell based on Spiro-ce comprises the following steps:
[0034] Step 1: Cleaning:
[0035] The ITO conductive substrate was cleaned with detergent, acetone, deionized water, and anhydrous ethanol ultrasonically in sequence, and dried with nitrogen; then treated with ultraviolet-ozone for 20 minutes to ensure that its surface was clean;
[0036] Step 2: Preparation of electron transport layer:
[0037] Firstly, isopropanol and deionized water are prepared into an isopropanol aqueous solution in a volume ratio of 1:1; the prepared isopropanol aqueous solution is mixed with a SnO2 aqueous solution in a volume ratio of 2.75:1, and a SnO2 solution is obtained by ultrasonic treatment; the prepared SnO2 solution is spin-coated on the ITO surface at a speed of 3000 rpm for 30 seconds, and then placed on a heating table and heated for 30 minutes at a temperature of 150°C;
[0038] Step 3: Prepare the perovskite light absorbing layer:
[0039] PbI2, PbBr, FAI, MABr, and CsI were added to a mixed solvent of DMF and DMSO in a volume ratio of 4:1 in a mass ratio of 31.05:4.36:10.76:1.24:1, and the mixture was stirred and mixed evenly. The obtained mixed solution was spin-coated on the electron transport layer obtained in step 2. The spin-coating conditions were as follows: first, spin-coating at a speed of 1300 rpm for 10 seconds, then spin-coating at a speed of 5000 rpm for 45 seconds, and 0.2 mL of chlorobenzene was added as an anti-solvent 15 seconds before the spin-coating was completed; after the spin-coating was completed, annealing was performed at 110°C for 60 minutes to obtain a perovskite light-absorbing layer;
[0040] Step 4: Preparation of hole transport layer:
[0041] The Spiro-ce prepared in Example 1 was added to chlorobenzene, stirred and mixed to obtain a Spiro-ce solution with a mass concentration of 110.04 mg / mL; 13.85 mg of Li-TFSI was added to 1 mL of the Spiro-ce solution, stirred and mixed to obtain a mixed solution; the obtained mixed solution was spin-coated on the perovskite light absorbing layer by a spin coating method, the spin coating speed was 3000 rpm, and the time was 30 s to obtain a hole transport layer;
[0042] Step 5: Prepare electrodes:
[0043] The device obtained in step 4 is placed in a vacuum evaporation chamber, and a 50 nm gold electrode is prepared on the surface of the hole transport layer by vacuum evaporation to obtain the perovskite solar cell.
[0044] Comparative Example 1
[0045] The difference between Comparative Example 1 and Example 2 is that: the process of preparing the hole transport layer in step 4 is specifically as follows: adding Li-TFSI to acetonitrile, stirring and mixing evenly, to obtain a Li-TFSI solution with a mass concentration of 520 mg / mL; adding Spiro-OMeTAD to chlorobenzene, stirring and mixing evenly, to obtain a Spiro-OMeTAD solution with a mass concentration of 72.3 mg / mL; measuring 17.5 μL of Li-TFSI solution and 28.8 μL of 4-tert-butylpyridine (TBP) and adding them to 1 mL of Spiro-OMeTAD solution, stirring and mixing evenly, to obtain a mixed solution; the obtained mixed solution is coated on the perovskite light absorbing layer by a spin coating method, the spin coating speed is 3000 rpm, and the time is 30 s, to obtain a hole transport layer.
[0046] After the perovskite solar cells prepared in Example 2 and Comparative Example 1 were placed for one week, the perovskite layer of the perovskite solar cell based on Spiro-OMeTAD (Comparative Example 1) had begun to degrade, while the perovskite solar cell based on Spiro-ce (Example 2) was basically the same as a week ago, and its air stability was greatly improved.
[0047] Figure 4 The performance comparison diagram of the perovskite solar cell prepared in Example 2 (Spiro-ce) and Comparative Example 1 (Spiro-OMeTAD). Figure 4 It can be seen that the perovskite solar cells based on Spiro-ce have the same excellent open circuit voltage (V oc ), short-circuit current density (J sc ), fill factor (FF).
[0048] Figure 5This is a performance comparison chart of the perovskite solar cell prepared in Example 2 after being placed for 1 hour and 120 hours. Figure 5 It can be seen that after the perovskite solar cell prepared in Example 2 is placed for a long time, its performance is basically not degraded and its stability is enhanced.
[0049] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment shall fall within the protection scope of the technical solution of the present invention.
Claims
1. A hole transport material containing a crown ether structure, characterized in that: The chemical structural formula of the hole transport material is: Wherein, n=1, 2 or 3; X is one or more of O or S.
2. A method for preparing a hole transport material containing a crown ether structure as claimed in claim 1, characterized in that: The following steps are involved: Step 1, add 2,2',7,7'-tetrabromo-9,9'-spirobifluorene, 4-methoxyaniline, sodium tert-butoxide, tri(dibenzylideneacetone)dipalladium, and tri(tert-butyl)phosphine into a three-necked flask, and then add anhydrous toluene; the obtained reaction mixture is stirred at 90-150° C. for 20-40 hours under nitrogen protection, and after completion, it is cooled to room temperature, filtered, and purified by silica gel column chromatography to obtain compound 1; wherein the molar ratio of 2,2',7,7'-tetrabromo-9,9'-spirobifluorene, 4-methoxyaniline, tri(dibenzylideneacetone)dipalladium, and tri(tert-butyl)phosphine is 1:(9.51-10.6):(0.26-0.38):(0.58-0.66); the structural formula of compound 1 is Step 2, compound 1, a material containing a crown ether group, sodium tert-butoxide, tri(dibenzylideneacetone)dipalladium, and tri(tert-butyl)phosphine are added to a three-necked flask, and then anhydrous toluene is added; the obtained reaction mixture is stirred at 90-150° C. for 20-40 hours under nitrogen protection, and after completion, it is cooled to room temperature, filtered, and purified by silica gel column chromatography to obtain a hole transport material containing a crown ether structure; wherein ... The molar ratio of palladium to ketone is 1:(4.98-5.97):(3.98-4.72):(0.29-0.41); the material containing crown ether group is 4-bromobenzo-12 crown 4-ether, 4-bromobenzo-15 crown 5-ether, 4-bromobenzo-18 crown 6-ether, or a material in which one or several oxygens of the crown ether group in 4-bromobenzo-12 crown 4-ether, 4-bromobenzo-15 crown 5-ether, 4-bromobenzo-18 crown 6-ether are replaced by sulfur.
3. A method for preparing a hole transport layer based on a hole transport material containing a crown ether structure, characterized in that: The following steps are involved: Step 1, adding the hole transport material containing a crown ether structure prepared by the method of claim 2 into an organic solvent, stirring and mixing evenly to obtain a mixed solution A with a mass concentration of 60 to 120 mg / mL; Step 2, adding Li-TFSI to the mixed solution A obtained in step 1, stirring and mixing evenly to obtain a mixed solution B; wherein the molar ratio of the hole transport material to Li-TFSI is 1: (0.02-0.08); Step 3: Spin coating the mixed solution B obtained in step 2 onto the perovskite light absorbing layer at a spin coating speed of 2000-4000 rpm for 20-40 s to obtain a hole transport layer.
4. The method for preparing a hole transport layer according to claim 3, characterized in that: The organic solvent in step 1 is chlorobenzene, dichlorobenzene, chloroform or toluene.
5. A perovskite solar cell, comprising a conductive substrate, an electron transport layer, a perovskite light absorbing layer, a hole transport layer and a metal electrode arranged in sequence, characterized in that: The hole transport layer is a hole transport layer prepared by the method according to claim 3 or 4.
Citation Information
Patent Citations
Optoelectronic component
CN105308768A
Perovskite cell based on ion-doped hole transport layer and preparation method of perovskite cell
CN111244284A
Composite material of hole-blocking polymer and electron-injection / electron-transport conjugated polymer grafted with crown ether into which metal ion is intercalated, and uses thereof in OLED and organic solar cell
US20130140527A1
Organic compound having cyclic structure
WO2012053444A1
